IMPLEMENTASI SIKAP TOLERANSI BERAGAMA ANTAR SESAMA MASYARAKAT DALAM INTERAKSI SOSIAL DI DESA RANSI DAKAN - Mardawani, Mardawani; Sejunsi, Botniaski; Puja, Puja (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to find out how people carry out social interactions amidst religious differences in Ransi Dakan village. In this research, the approach used is a qualitative approach, namely by observing the activities that residents carry out and working together with the Ransi Dakan community. The aim is to find out the character of each community in Ransi Dakan Village. The data analysis technique begins with observing and interacting with local residents through communication. The results of this research show that community interactions still have an attitude of tolerance between religious communities that is still well maintained. People carry out religious activities in accordance with the religion they believe in. Activities in terms of cooperation and mutual cooperation are carried out by the community together, without distinguishing between the beliefs held by other individuals. In terms of accommodation, people always respect and respect each other, such as during religious holiday activities including Islam, Hinduism, Christianity, Catholicism and religious beliefs. Meanwhile, in terms of assimilation, people are able to accept the religious differences that exist in their families, the result of interfaith marriages.Â Keywords: Social interaction, tolerance, religionÂ Â